2010
DOI: 10.1111/j.1745-4514.2010.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinolytic Serine Proteinases From the Wing Muscle of Red Stingray

Abstract: Four gelatinolytic proteinases (A1, 97 kDa; A2, 66 kDa; A3, 30 kDa; A4, 23 kDa) were detected from the red stingray wing muscle by gelatin zymography. Among these proteinases, major gelatinolytic proteinases (A1, A2) were more purified and examined their characters. The optimum pH and temperature for the gelatinolytic activity of A1 and A2 were around pH 7 and pH 8, and maximal activity of A1 is at 30–50C, that of A2 is at 30C. Also, they were demonstrated to hydrolyze the gelatin from red stingray; protein ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Gelatinolytic serine proteinases were detected in the red stingray wing muscle by gelatin zymography [7]. In our previous study, we also found gelatinolytic enzymes including a trypsin-type serine proteinase (G1) and two metalloproteinases (G2 and G3) in red sea bream muscle [8].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Gelatinolytic serine proteinases were detected in the red stingray wing muscle by gelatin zymography [7]. In our previous study, we also found gelatinolytic enzymes including a trypsin-type serine proteinase (G1) and two metalloproteinases (G2 and G3) in red sea bream muscle [8].…”
Section: Introductionmentioning
confidence: 76%
“…The solubilization of type V collagen was reported to be involved in softening of sardine muscle during chilled storage [3]. Also, gelatinolytic enzymes which degrades gelatin, denatured collagen, have been investigated in various fish [4][5][6][7][8]. Metalloproteinases and serine proteinases have been detected in various organs of yellowtail [4] and Atlantic cod [5].…”
Section: Introductionmentioning
confidence: 99%
“…2), which is similar to the gelatinolytic proteinases from common carp muscle (Wu et al . 2008), red stingray muscle (Bae et al . 2010) and red sea bream muscle (Wu et al .…”
Section: Discussionmentioning
confidence: 99%
“…2000), Atlantic cod ( Gadus morhua ), spotted wolfish ( Anarhichas minor ) and Atlantic salmon ( Salmo salar ) (Lødemel and Olsen 2003). Gelatinolytic serine proteinases were detected in many fish species by gelatin zymography, including red stingray wing ( Dasyatis akajei ) (Bae et al . 2010), red sea bream ( Pagrus major ) (Yoshida et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation